P9 A randomised, double-blind, parallel group, placebo-controlled trial of metformin in tuberous sclerosis complex. (12th March 2018) - Amin, S; Mallick, AA; Edwards, H; Lux, A; Laugharne, M; Likeman, M; Khan, A; O'Callaghan, F
Abstract : Introduction: Tuberous Sclerosis Complex (TSC) is a genetic disorder characterised by the development of benign tumours, secondary to the loss of inhibitory regulation of the mTOR (mammalian Target Of Rapamycin) intracellular growth pathway. Metformin inhibits the mTOR pathway. We investigated the effect of Metformin in patients with TSC. Methods: This was a multicentre randomised, double-blind, parallel group, placebo-controlled trial of metformin in children and adults with TSC. Patients were randomly allocated to placebo or metformin (1:1) for 12 months. The main outcomes were percentage volume change of renal angiomyolipomas (AML) and cerebral Subependymal Giant Cell Astrocytomas (SEGA). Blinded MRI assessments of AMLs and SEGAs were performed at baseline and at 12 months. Results: Fifty-one patients participated, of whom 43 were adults (age range 10–50 years, median age 27, IQR 17). 24 received placebo and 27 received metformin. The mean AML volume increase from baseline was 25.5% for the placebo group and 9.6% for the metformin group. Difference in response, 15.9% (95% CI −9% to 41%) p=0.221. Twenty-seven patients had SEGAs: 13 received placebo and 14 metformin. The mean SEGA volume increased from baseline by 37% in the placebo group but reduced from baseline by 23.3% in the metformin group. Difference in response, 60.3% (95% CI −0.4% to 111, p=0.048). Three serious adverse events occurred that reflected the underlying disease. Two were AML haemorrhages and one was worsening seizures requiring hospitalisation. Conclusions: Metformin is safe and well tolerated in children and adults with TSC. Patients on metformin had a significant reduction in SEGA volume compared with placebo. Metformin did not reduce AML size but growth appeared slower than in the placebo group, although this difference was not statistically significant. There may be a role for metformin in slowing or reversing the growth of life-threatening hamartomas in TSC. Further study is justified.